2009
DOI: 10.1007/s10532-009-9315-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biodegradation and decolorization of Direct Orange 39 (Orange TGLL) by an isolated bacterium Pseudomonas aeruginosa strain BCH

Abstract: A newly isolated novel bacterium from sediments contaminated with dyestuff was identified as Pseudomonas aeruginosa strain BCH by 16S rRNA gene sequence analysis. The bacterium was extraordinarily active and operative over a wide rage of temperature (10-60 degrees C) and salinity (5-6%), for decolorization of Direct Orange 39 (Orange TGLL) at optimum pH 7. This strain was capable of decolorizing Direct Orange 39; 50 mg l(-1) within 45 +/- 5 min, with 93.06% decolorization, while maximally it could decolorize 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…The phytotoxicity study carried out at room temperature on Allium sativum show considerable decrease in growth in presence of higher concentration of dye (Table 3.6). Similar results were observed by (Jadhav et al 2009) 10 on % germination of both Triticum aestivum and Phaseolus mungo seeds with Direct Orange 39 as compared with its degraded metabolites. The phytotoxicity study showed that length of plumule and radical was affected in case of the dye Direct Orange 39 whereas with degraded metabolites it showed significant growth, compared to control which indicate that, the isolated Pseudomonas aeruginosa strain BCH was not only able to decolorize Direct Orange 39 but was also able to detoxify it.…”
Section: Effect Of Co-substrates In Mediumsupporting
confidence: 88%
“…The phytotoxicity study carried out at room temperature on Allium sativum show considerable decrease in growth in presence of higher concentration of dye (Table 3.6). Similar results were observed by (Jadhav et al 2009) 10 on % germination of both Triticum aestivum and Phaseolus mungo seeds with Direct Orange 39 as compared with its degraded metabolites. The phytotoxicity study showed that length of plumule and radical was affected in case of the dye Direct Orange 39 whereas with degraded metabolites it showed significant growth, compared to control which indicate that, the isolated Pseudomonas aeruginosa strain BCH was not only able to decolorize Direct Orange 39 but was also able to detoxify it.…”
Section: Effect Of Co-substrates In Mediumsupporting
confidence: 88%
“…For example, some Pseudomonas sp. have recently been described for their abilities to degrade dyes such as Malachite Green and Direct Orange 39 (Orange TGLL) with such lignases as peroxidases [Du et al, 2011;Jadhav et al, 2010], thus explaining why our Pseudomonas sp. also has good potential for industrial degradation of lignocellulosic biomass.…”
Section: Discussionmentioning
confidence: 97%
“…During maximum growth, maximum enzyme production was achieved which are responsible for melanoidin decolorization by microorganism. Maximum growth also inhibits melanoidin decolorization due to production of some other enzymes or metabolites by the microorganism as a feedback inhibition mechanism during metabolism (Jadhav et al, 2011). In the present investigation, bacterial strains showed maximum decolorization in a very short period i.e.…”
Section: Discussionmentioning
confidence: 46%